COVID-19 related stressors and mental health outcomes of expatriates in international construction - Gao, Lili; Deng, Xiaopeng; Yang, Weimin; Fang, Jie (Frontiers in Public Health, 2022)
The construction industry is labor-intensive, and employees' mental health has a significant impact on occupational health and job performance. In particular, expatriates in international projects under the normalization of the epidemic are under greater pressure than domestic project employees. This paper aims to explore the association of stressors and mental health in international constructions during COVID-19. Furthermore, test the mediation effect of psychological resilience and moderating effort of international experience in this relationship. A survey of 3,091 expatriates in international construction projects was conducted. A moderating mediation model was employed to test the effect of psychological resilience and international experience. Then, statistical analysis with a bootstrap sample was used to test the mediation effect of the model, and a simple slope was used to test the moderating effect. Moderated by experience, the slope of the effect of stressors on psychological resilience changed from −1.851 to −1.323. And the slope of the effect of psychological resilience on mental health outcomes reduced by about 0.1. This suggests that experience is one of the buffering factors for individual psychological resilience of expatriates to regulate stress. Theoretically, this study verifies the mediation effect of psychological resilience between COVID-19 related stressors and mental health outcomes and importance of an expatriate's experience in an international assignment. Practically, this study provides guidelines for international construction enterprises and managers to make an assistant plan for expatriates during this pandemic time and pay more attention to their psychological status. The research also suggests that the best choice for challenging assignments is choosing a more experienced employee.